Peculiarities of “entrepreneurial spirit” forming of the main character in the story “Gava” by I. (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article represents the specificity of the character entrepreneurial relations among the small entrepreneurs at the end of the nineteenth century described by means of the artistic words in the story “Gava” by I. Franko. This paper is an attempt to reveal the essence of the entrepreneurial phenomenon on the example of story "Gava" by I. Franko. It also shows the reasons, motives and conditions of the "entrepreneurial spirit" formation among the representatives of such a social stratum, as retailers and entrepreneurs. The component analysis of “Gava” story allows to define the specific way of the entrepreneurial feature formation of the main character in the story “Gava” by I. Franko and to find out the peculiarities of the economic knowledge formation among the recipients by means of artistic word. The main character of the story obtains the following features as initiative, determination, and wit. It should be noted that Gava has a very well-developed intuition, which significantly contributes to his rational and entrepreneur actions. Gava's actions and behaviour show commercial and managerial abilities that correlate well enough with his ingenuity, as he is constantly looking for new ways and methods of earning money, opening up new areas of capital application.
Keywords: entrepreneurship; economic relations; character; business; entrepreneurial spirit